2023
DOI: 10.1097/mnm.0000000000001694
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac atrial metabolism quantitative assessment with analog and digital time of flight-PET/computed tomography

Abstract: Background Evaluation of left atrium (LA) remodeling is becoming increasingly relevant in understanding several pathological cardiac conditions. 18 F-FDG-PET/computed tomography (CT), the current gold standard for metabolic evaluation of the left ventricle, could be extended to LA using the latest PET technologies. We sought to perform a phantom study to optimize the reconstruction algorithm in this context. MethodsThe liver, heart cavity and walls of an anthropomorphic phantom were filled with typical patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Recent improvements in PET technology have enabled higher spatial resolution and improved image quality, thereby allowing for the acquisition of high-quality PET images of the atria without influence of partial volume effect. 5 Our study is novel in that it prospectively used this technique to explore the metabolic changes in the atria of patients with persistent AF in comparison with those with restored SR. Although some previous studies have reported increased FDG uptake in atria of patients with AF, 6 , 7 , 8 , 9 , 10 the type of AF (ie, paroxysmal vs persistent varied); importantly, these studies were not performed under well-standardized metabolic conditions, but usually only after fasting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent improvements in PET technology have enabled higher spatial resolution and improved image quality, thereby allowing for the acquisition of high-quality PET images of the atria without influence of partial volume effect. 5 Our study is novel in that it prospectively used this technique to explore the metabolic changes in the atria of patients with persistent AF in comparison with those with restored SR. Although some previous studies have reported increased FDG uptake in atria of patients with AF, 6 , 7 , 8 , 9 , 10 the type of AF (ie, paroxysmal vs persistent varied); importantly, these studies were not performed under well-standardized metabolic conditions, but usually only after fasting.…”
Section: Discussionmentioning
confidence: 99%
“…FDG PET/CT was performed using a high-resolution digital 64 slice PET/CT system (Vereos TOF- Philips Healthcare) using a previously optimized protocol to enable the reconstruction of high-resolution atrial PET images. 5 Patients were studied after overnight fasting and received a nicotinic acid derivative (acipimox 250 mg) to maximally stimulate myocardial glucose uptake. Before tracer injection levels of fasting glucose, insulin, and free fatty acids were measured in venous blood samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation